(BOAS) PRÁTICAS NA CRECHE: MIRADAS EMERGENTES SOBRE A CRIANÇA E A INFÂNCIA - NASCIMENTO, BEATRIZ DA SILVA FALEIRO DO (2017)
This study aims at evaluating different viewpoints on the concept of (good) practice in nursery schools based on the narrative of the researcher about her formative experiences and with small children, on the narratives of two teachers who work in nursery classes and on the narratives of three elementary school teachers who have already worked in nursery classes, all in institutions of São Bernardo do Campo, SP, apart from scenes observed in a nursery class of the same city. The initial premise was the hypothesis that there is complexity (MORIN, 2015b) in the concepts of (good) practices and that these concepts are related to the conceptions of childhood of the theories and evaluated subjects.In order to understand the substance of this premise, this research was inspired by a mirror-oriented metaphor and based on the methodological approach of Narrative Research (CLANDININ, CONNELLY, 2011).The gazes in the mirror intended to relate, at first, the narratives of the teachers to the concept of childhood in the slant of the sociology of childhood.Thus, this study was also based on childhood reaserchers, such as Sarmento (2004) and Larrosa (2003), on nursery teachers formation, and on the analysis of some documents that rule educational institutions in Brazil.During the research, the position of Moss (2002) regarding the discussion of the concept of quality, or of what isgood in the nursery, was also considered.The gazes in the field text allowed the re-signification of the concept of (good) practices with a look from a new paradigm.The study broadens the horizons of the Emergent Paradigm (MORAES, 2010), proposing gazes of (good) practices in nursery school in the perspective of a paradigm that emerges from the gaze of the child and the voice of childhood as an integral being and that therefore favors practices which are meant to come out as integral